2012
DOI: 10.1590/s0004-27492012000300011
|View full text |Cite
|
Sign up to set email alerts
|

Profile of ocular and systemic characteristics in Möbius sequence patients from Brazil and Italy

Abstract: Adverse events during pregnancy varied between both groups. A history of misoprostol use during early pregnancy was present only in Brazilian mothers, who had lower levels of education and less frequent stable marital statuses. Clinical findings were similar between both groups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
3
16
2
Order By: Relevance
“…A previous study of patients with Mobius sequence reported a male: female ratio of 1.3:1, which was similar to the results of our study (31) . In the northeastern region of Brazil, the mothers of children with Möbius sequence took 600 to 2,800 µg of misoprostol between the fourth and sixth postfertilization week (7) .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A previous study of patients with Mobius sequence reported a male: female ratio of 1.3:1, which was similar to the results of our study (31) . In the northeastern region of Brazil, the mothers of children with Möbius sequence took 600 to 2,800 µg of misoprostol between the fourth and sixth postfertilization week (7) .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, teratogens could be identified in most cases (56%), and 9.8% of the mothers were exposed to more than one teratogen. Furthermore, an isolated rubella infection during pregnancy was reported by one of the mothers.A previous study of patients with Mobius sequence reported a male: female ratio of 1.3:1, which was similar to the results of our study (31) . In the northeastern region of Brazil, the mothers of children with Möbius sequence took 600 to 2,800 µg of misoprostol between the fourth and sixth postfertilization week (7) .…”
supporting
confidence: 93%
See 3 more Smart Citations